Determinants of current hand eczema: results from case-control studies nested in the PACO follow-up study (PACO II) - Apfelbacher, Christian; Funke, Ulrich; Radulescu, Magda; Diepgen, Thomas L. (Contact dermatitis, 2010)
Background: Hand eczema is often a result of the interplay of exogenous and endogenous risk factors. Epidemiological studies demonstrating the interrelationship between these factors are lacking. Objective: To analyse risk factors associated with current hand eczema and current irritant hand eczema in two case-control studies nested in a long-term follow-up study in the car industry. Patients/Materials/Methods: Eligible participants were individuals who had been followed until the end of their apprenticeship in the original cohort study (1990-1998, N = 1909). Participants were interviewed and underwent dermatological examination. Two case-control studies were nested within the cohort, one using current hand eczema cases (n = 110) and one using current irritant hand eczema cases (n = 57). Multivariable modelling was performed. Results: The only significant finding was a positive association of atopic skin diathesis with hand eczema in both studies. Wet work ≥2 hr/day was positively related to current irritant hand eczema. Age and having an office job were inversely related to hand eczema. Conclusions: Atopic skin diathesis was the most important determinant of hand eczema. Constitution seems to play a dominant role compared with environmental and occupational hazards in a setting where skin protection measures are well established.
Gesehen am 24.11.2022